2018
DOI: 10.3390/ijerph15050997
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Sleep Duration and Overweight/Obesity among Adolescents in a Chinese Population

Abstract: Objectives: The objective of this study was to investigate the relationship between sleep duration and overweight/obesity among Chinese adolescents. Methods: A school-based cross-sectional study was conducted among Chinese adolescents in 2016. In total, 2795 school-aged Chinese children aged 12 to 13 years participated in this study. Participants were asked to complete self-administered surveys during a 45-min class period in their classroom. Details of the questionnaire about health-related behaviors included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…Substantial concrete evidence indicated that there was a significant negative effect on the individual's sleep health when people engaged in health-related risk behavior(s) [19,20,32,33]. This study concluded that with an increase in health-related risk behaviors, the negative effects on sleep health could be further increased, at least for both the increased prevalence of sleep problems and the deterioration of sleep quality.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Substantial concrete evidence indicated that there was a significant negative effect on the individual's sleep health when people engaged in health-related risk behavior(s) [19,20,32,33]. This study concluded that with an increase in health-related risk behaviors, the negative effects on sleep health could be further increased, at least for both the increased prevalence of sleep problems and the deterioration of sleep quality.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies from developed countries or regions have confirmed the link between specific behaviors and sleep health. Health-related behavioral risk factors, including tobacco use, alcohol drinking, unhealthy dietary behaviors, as well as insufficient time for leisure activities and physical inactivity, have been shown to be associated with sleep health [17,19,20,32,33]. The results of these studies provide the theoretical basis for developing interventions that specifically target a particular health-related risk behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Short sleep duration is very common in modern society, with approximately onethird to two-thirds of adolescents complain about insufficient sleep (8)(9)(10). Although emerging evidences from both crosssectional and longitudinal studies have indicated the close relationship between short sleep duration and obesity (11)(12)(13), including in Chinese children (14)(15)(16)(17), studies focusing on the relationship between sleep duration and abdominal obesity are still limited. Recently, several studies found that sleeping longer on weekends may help ameliorate some of the effects of insufficient sleep during the weekdays, which suggested that weekday-weekend variability in sleep duration may play a role in overweight and obesity (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements In the general health examination, the height and body weight of all participants were measured by trained research staff. Details of the examination have been described in a previous publication of our group [15]. Body mass index (BMI) was calculated using the ratio of weight/height 2 (kg/m 2 ).…”
Section: Measures Eating Speed and Other Behaviorsmentioning
confidence: 99%